2017
DOI: 10.3390/molecules22030362
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Disulfide-Rich Venom Peptides with Ion Channels and Membranes

Abstract: Disulfide-rich peptides isolated from the venom of arthropods and marine animals are a rich source of potent and selective modulators of ion channels. This makes these peptides valuable lead molecules for the development of new drugs to treat neurological disorders. Consequently, much effort goes into understanding their mechanism of action. This paper presents an overview of how molecular simulations have been used to study the interactions of disulfide-rich venom peptides with ion channels and membranes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 115 publications
(205 reference statements)
0
9
0
Order By: Relevance
“…Throughout the simulation, FEP retains all degrees of freedom to account for conformational variation in ligand-receptor interactions and permits the displacement and introduction of explicit waters [ 23 ], which can result in a significant increase in accuracy over other predictive methods, such as Molecular mechanics-generalized born/surface area (MM-GB/SA), in which the protein is fixed and an implicit representation of the solvent is used [ 24 , 25 ]. The major drawback of FEP until recently was that it was computationally costly [ 26 ]. However, recent implementations of FEP that run on graphical processor units (GPUs) are significantly faster [ 27 ] and two recent studies found that FEP could predict the ΔΔG EXP for dozens of mutations made to interacting proteins [ 25 ] and neutralizing antibodies [ 21 ] with a root-mean-squared error (RMSE) and mean-unsigned error (MUE) approaching the experimental limit of 1 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the simulation, FEP retains all degrees of freedom to account for conformational variation in ligand-receptor interactions and permits the displacement and introduction of explicit waters [ 23 ], which can result in a significant increase in accuracy over other predictive methods, such as Molecular mechanics-generalized born/surface area (MM-GB/SA), in which the protein is fixed and an implicit representation of the solvent is used [ 24 , 25 ]. The major drawback of FEP until recently was that it was computationally costly [ 26 ]. However, recent implementations of FEP that run on graphical processor units (GPUs) are significantly faster [ 27 ] and two recent studies found that FEP could predict the ΔΔG EXP for dozens of mutations made to interacting proteins [ 25 ] and neutralizing antibodies [ 21 ] with a root-mean-squared error (RMSE) and mean-unsigned error (MUE) approaching the experimental limit of 1 kcal/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking has been the major SB methodology to predict affinities to macromolecular targets, to interpret binding modes, and to assist in the design of drug leads. Several recent publications illustrate the application of the method to MNPs [ 127 , 128 , 129 , 138 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ], and some representative examples are here described.…”
Section: Computer-aided Drug Design (Cadd)mentioning
confidence: 99%
“…Peptides and proteins with structural properties that deviate from the norm can pose challenges for biomolecular simulations [51][52][53]. Molecular dynamics (MD) simulations are extensively used to study peptides and their interactions with proteins or biological membranes [53][54][55][56][57]. The accuracy of properties obtained from MD simulations, amongst other factors, strongly depends on the force field used [51,52,58,59].…”
Section: /48mentioning
confidence: 99%